TANTANGAN GLOBAL DAN UPAYA MENUJU MANAJEMEN PERGURUAN TINGGI YANG EFISIEN - mulyono, mulyono (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2016)
Globalization challenging blows the life of university, tertiary educational institution that has main activity in high educational conversation with academic activity which commonly has universal concepts and adoptive ability in order to balance with the condition and Indonesia situation. Now days, tertiary educational institution is focused on the real big transformation era and it can not be denied anymore that the university must accept it if want surviving, striving, and developing. Solving those problems, many ideas are explored, such as economic concept and decentralization. The other opinion as the alternative is Interpreneurial University (EU) that is the university which has entrepreneurship character. Nevertheless, whatever concept and development management strategy of university that has already been tested is able to be applied therefore basically; everything must be based on efficiency principle. This point is an important to build the efficient management in university.Key Words: Challenging, management, university Efficiency